Optimal Sewer Network Design for Cities in Hilly Regions - Saldarriaga, Juan; Herrán, Juana; Iglesias-Rey, Pedro L. (Urban water journal, 2023)
This paper proposes a method to include drop manholes in the optimal design of sewer networks. These structures dissipate energy and reduce flow velocity, which is important in hilly regions where high slopes induce velocities that exceed the maximum allowable. The methodology proposed here introduces a new type of arc to represent drop manholes in a model that uses graph theory to achieve the minimum cost design of a sewer network. Also, for the estimation of drop manhole costs, a new cost function is developed based on pipe and manhole cost equations proposed in the literature. The methodology was tested in eight different series of pipe configurations, as well as a real sewer network located in Colombia, varying the pipe material and the land slope. The results demonstrated that the proposed methodology allows for the optimal design of sewer networks in hilly regions while satisfying all hydraulic and commercial constraints.